TRIM17 and TRIM28 antagonistically regulate the ubiquitination and anti-apoptotic activity of BCL2A1 - Lionnard, Loïc (Cell Death Differ, 2018)
BCL2A1 is an anti-apoptotic member of the BCL-2 family that contributes to chemoresistance in a subset of tumors. BCL2A1 has a short half-life due to its constitutive processing by the ubiquitin–proteasome system. This constitutes a major tumor-suppressor mechanism regulating BCL2A1 function. However, the enzymes involved in the regulation of BCL2A1 protein stability are currently unknown. Here, we provide the first insight into the regulation of BCL2A1 ubiquitination. We present evidence that TRIM28 is an E3 ubiquitin-ligase for BCL2A1. Indeed, endogenous TRIM28 and BCL2A1 bind to each other at the mitochondria and TRIM28 knock-down decreases BCL2A1 ubiquitination. We also show that TRIM17 stabilizes BCL2A1 by blocking TRIM28 from binding and ubiquitinating BCL2A1, and that GSK3 is involved in the phosphorylation-mediated inhibition of BCL2A1 degradation. BCL2A1 and its close relative MCL1 are thus regulated by common factors but with opposite outcome. Finally, overexpression of TRIM28 or knock-out of TRIM17 reduced BCLA1 protein levels and restored sensitivity of melanoma cells to BRAF-targeted therapy. Therefore, our data describe a molecular rheostat in which two proteins of the TRIM family antagonistically regulate BCL2A1 stability and modulate cell death.